Map of cleaning procedures and response actions to oil spills - Romero, A. F. [UNESP]; Abessa, D. M.S. [UNESP] (My University, 2014)
When an oil spill occurs, the information available in the emergency plan allows the definition of the best strategies for containment and removal of oil slick from water before it reaches the coastal environments. Despite such efforts, oil slicks often have reached the coast, requiring cleaning actions. Currently, information on the recommended cleaning procedures in contingency plans is not easily visualized in ESI maps. This paper presents a proposal to develop maps of cleaning procedures and response actions to oil spills in order to facilitate rapid viewing of the recommended cleaning procedures. The study area is located in the estuarine complex of Cananeia, Sao Paulo State. Brazil. This area is characterized by high ecological and social importance, with the presence of protected areas and mangroves. The sensitivity of the environments was obtained through the ESI maps. Cleaning procedures were determined for each environment, and icons were created for all possible cleaning procedures. Then the information about sensitivity and cleaning procedures were combined into GIS to generate the maps. The map of cleaning procedures and response actions is an innovative tool that can be used in the planning of the actions and during an oil spill, helping managers and emergency responders to take rapid and effective decisions to minimize the impacts of the oil.